2022
DOI: 10.3390/su14095674
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Transport Exclusion on the Local Development of Biała County

Abstract: The issue of transport exclusion is an important social problem. It is of major interest to both central and local authorities. For the purposes of this study, a research questionnaire was conducted on the issue of transport exclusion. The area of the research carried out was Biała County, composed of seventeen communes and two cities. The data were collected based on an electronic questionnaire, i.e., using the CAWI method (Computer Assisted Web Interview). In total, 473 inhabitants of the studied area took p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…So far, while many recommendations regarding green and sustainable transport organization and prioritization have been advertised [36], no comprehensive catalogue of guidelines has been developed to support designers and strategic decision-makers in resource-constrained situations, such as those where small transport hubs are built, as well as those specifically tailored to such hubs. Such situations are faced by people in locations considered remote, far away from large cities, as indicated by Charnavalau et al, who investigated transport exclusion and observed that the groups most disadvantaged by this are the elderly and people with disabilities, especially in small towns [37]. The transport-related social exclusion of the elderly was explored by Shergold and Parkhurst [38], who also found this group to be particularly vulnerable when their transportation needs are not met.…”
Section: Sustainability Solutions In Small Transport Hub Designmentioning
confidence: 98%
See 1 more Smart Citation
“…So far, while many recommendations regarding green and sustainable transport organization and prioritization have been advertised [36], no comprehensive catalogue of guidelines has been developed to support designers and strategic decision-makers in resource-constrained situations, such as those where small transport hubs are built, as well as those specifically tailored to such hubs. Such situations are faced by people in locations considered remote, far away from large cities, as indicated by Charnavalau et al, who investigated transport exclusion and observed that the groups most disadvantaged by this are the elderly and people with disabilities, especially in small towns [37]. The transport-related social exclusion of the elderly was explored by Shergold and Parkhurst [38], who also found this group to be particularly vulnerable when their transportation needs are not met.…”
Section: Sustainability Solutions In Small Transport Hub Designmentioning
confidence: 98%
“…The study's findings can be applied to the sustainability-focused design of transport hubs in small cities with deficiencies in public transport. The problem of transport exclusion in such cities [42] is universal [37,[43][44][45] and has been approached in our study in a manner that can be easily adapted to local, case-specific conditions in most cultures and climates.…”
Section: Objective Of the Studymentioning
confidence: 99%
“…The basic idea, which is verified by experience, suggests that low access to mobility can reduce the opportunity to participate in society, which also negatively affects a person's health and overall sense of well-being (Delbosc & Currie, 2011;Mackett & Thoreau, 2015;Ma et al, 2018). Inspiring ideas about the social impacts of poor transport accessibility for populations living in peripheral areas and/or with limited mobility options are also reflected, with some time lag, in the work of authors from post-socialist states (Horňák & Rochovská, 2014;Gašparović, 2016;Jaroš, 2017;Székely & Novotný, 2020Baran & Augustyn, 2021;Charnavalau et al, 2022;van Dülmen et al, 2022) or from other parts of Europe (Binder & Matern, 2020).…”
Section: Introductionmentioning
confidence: 99%